4-Aninomethylbicyclo[2.2.2]-Octane-1-Carboxylic Acid a New Potent Antifibrinolytic Agent - Baumgarten, W; Priester, L. I; Stiller, D. W; Duncan, A. E. W; Ciminera, J. L; Loeffler, L. J (Thrombosis and Haemostasis, 1969)
In this publication we describe a new antifibrinolytic compound, 4-aminomethyl-bicyclo[2.2.2]-octane-l-carboxylic acid. This compound is the most active antifibrinolytic agent known up to the present.Its activity has been characterized by two in vitro assay procedures and its relative potency compared to the standard antifibrinolytic agent, ε-aminocaproic acid.Two assay procedures for the evaluation of antifibrinolytic compounds have been developed with particular emphasis on the capability to yield statistically valid results.